Bridging the Gap: The Nexus between Public Administration and the Defense Sector - Sarjito, Aris (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
This qualitative research explores the obstacles to coordinating and communicating between public administration and the defense sector, utilizing secondary data to assess the effectiveness of bridging the gap. The research findings reveal significant challenges hindering effective collaboration, emphasizing the need for improved communication channels. Strategies to enhance knowledge transfer and expertise between public administration and the defense sector are discussed. The study identifies a lack of mutual understanding as a primary obstacle and proposes actionable measures to address this gap. In conclusion, the research emphasizes the significance of fostering a stronger connection between public administration and the defense sector for enhanced national security and democratic governance.